Auditoria en Seguridad Vial (ASV) Variante Condina Km 6 + 500 al Km 13 + 000 municipio de Pereira Risaralda (2022)
This document contains the development of the ASV. Variante Condina, section Km 6 + 500 to the Km 13 + 000 to the variables: vehicular containment barriers, geometric design and signage. The descriptive quantitative methodology was produced, the variables were operationalized, the state of the art, theoretical and conceptual.